2022
DOI: 10.3390/gels8080494
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Grafted Poly (Ethylene Glycol) Methyl Ether Acrylate Particulate Hydrogels for Drug Delivery Applications

Abstract: Chitosan (CS) crosslinking has been thoroughly investigated, but the chemical reactions leading to submicronic hydrogel formulations pose problems due to various physical/chemical interactions that limit chitosan processability. The current study employs the chemical modification of chitosan by Michael addition of poly (ethylene glycol) methyl ether acrylate (PEGA) to the amine groups to further prepare chitosan particulate hydrogels (CPH). Thus, modified CS is subjected to a double crosslinking, ionic and cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…The C=O of the carboxyl group increased in intensity as the concentration of IA increased in the samples [41] . The absorption peak at 1120 cm −1 belonged to the stretching vibration peak of C−O−C in OEGA [42] . It could be seen about 3435 cm −1 and 3080 cm −1 as broad bands for O−H and secondary N−H amide.2972 cm −1 , 2928 cm −1 , and 2874 cm −1 were the C−H stretching vibration peak for isopropyl groups.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The C=O of the carboxyl group increased in intensity as the concentration of IA increased in the samples [41] . The absorption peak at 1120 cm −1 belonged to the stretching vibration peak of C−O−C in OEGA [42] . It could be seen about 3435 cm −1 and 3080 cm −1 as broad bands for O−H and secondary N−H amide.2972 cm −1 , 2928 cm −1 , and 2874 cm −1 were the C−H stretching vibration peak for isopropyl groups.…”
Section: Resultsmentioning
confidence: 90%
“…[41] The absorption peak at 1120 cm À 1 belonged to the stretching vibration peak of CÀ OÀ C in OEGA. [42] It could be seen about 3435 cm À 1 and 3080 cm À 1 as broad bands for OÀ H and secondary NÀ H amide.2972 cm À 1 , 2928 cm À 1 , and 2874 cm À 1 were the CÀ H stretching vibration peak for isopropyl groups. A peak at 1650 cm À 1 was assigned to a strong C=O amide I band, and at 1545 cm À 1 for another strong amide II band.…”
Section: Synthesis and Characterizationmentioning
confidence: 93%
“…As reported in our previous study, we chemically modified CS with PEGA using Michael’s addition reaction under the same conditions [ 26 , 35 ]. To make CS-PEGA, CS (2.0 g) was dissolved in 100 mL of 1% ( w / w ) acetic acid solution in a 250 mL flask with a reflux condenser.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the combination of tripolyphosphate and sulfate as crosslinking agents produced smaller and spherical chitosan-Fe 3 O 4 particles [ 24 ]. Different studies showed that CS-based NPs could encapsulate and release different types of drugs at a constant rate, which showed the potential of CS as a sustained-release matrix polymer [ 10 , 16 , 17 , 23 , 25 , 26 ]. Levofloxacin and ciprofloxacin are two antibiotics from the second-generation quinolones.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, micelles constructed of amphiphilic block polymers such as PEGMA have been widely studied in drug administration with the goal of tumor‐targeted theranostics. [ 23–35 ] Polymeric nanocomposites containing zinc oxide can help prepare biocompatible nanoparticles and effectively deliver chemotherapy drugs to cancer cells. Many studies have shown that Zinc oxide nanoparticles can be used to provide chemotherapy agents as a cancer treatment.…”
Section: Introductionmentioning
confidence: 99%